Clinical and molecular characteristics of a Brazilian family with spinocerebellar ataxia type 1 - Lopes-Cendes,Iscia (1996)
The spinocerebellar ataxias (SCAs) are a clinically and genetically heterogeneous group of late onset neurodegenerative disorders. To date, seven different genes causing autosomal dominant SCA have been mapped: SCA1, SCA2, Machado-Joseph disease (MJD)/SCA3, SCA4, SCA5, SCA7 and dentatorubropallidoluysian atrophy (DRPLA). Expansions of an unstable trinucleotide CAG repeat cause three of these disorders: SCA1, MJD/SCA3 and DRPLA. We studied one Brazilian family segregating an autosomal dominant type of SCA. A total of ten individuals were examined and tested for the presence of the SCA1, MJD and DRPLA mutations. Three individuals, one male and two females, were considered affected based on neurological examination; ages at onset were: 32, 36 and 41 years. The first complaint in all three patients was gait ataxia which progressed slowly over the years. Six individuals showed one allele containing an expanded CAG repeat in the SCA1 gene. The mean size of the expanded allele was 48.2 CAG units. Instability of the expanded CAG tract was seen in the two transmissions that were observed in this family. In both occasions there was a contraction of the CAG tract. Our study demonstrates that SCA1 occurs in the Brazilian population. In addition, our results stress the importance of molecular studies in the confirmation of diagnosis and for pre-symptomatic testing in SCAs.